GENETIC PREDISPOSITION TO BRONCHOPULMONARY PATHOLOGY - Andrushchenko, T.A.; Stroy, D.O.; Goncharov, S.V.; Dosenko, V.E.; Ishhejkin, K.E. (World of Medicine and Biology, 2019)
We studied 215 people who work in harmful industries, 90 of which had a history of bronchopulmonary pathology of occupational etiology and 125 of them without such pathology. The following polymorphisms of DNA repair genes were identified in real-time using polymerase chain reaction: XPD (rs13181, rs799793), ERCC1 (rs11615), XRCC3 (rs861539), XRCC1 (rs25487), ATM (rs664677), XRCC7 (rs7003908) and MLH1 (rs1799977). We studied the frequency distribution of the genotypes of DNA repair genes with the subsequent integral statistical analysis of the data obtained. Analysis of the results made it possible to build a mathematic model that included two single nucleotide polymorphisms: XRCC1 (rs25487) and ATM (rs664677), which in this study represented the two main independent effects with the greatest predictive power 80.35 % for the results of binary logistic regression and of the method of multivariate dimension reduction.